Attempt to correlate simulations and measurements of turbine performance under pulsating flows for automotive turbochargers - Avola, Calogero (2020)
The paper attempts to correlate simulations and measurements of turbine performance under pulsating flows for automotive turbochargers. Under real automotive powertrain conditions, turbochargers are subjected to pulsating flows, due to the motion of the engine’s valves. Experiments on a purpose-built 2.2 L diesel engine gas-stand have allowed the quantification of unsteady pulsating turbine performance. Temperature, pressure and mass flow measurements are fundamental for the characterisation of turbine performance. An adequate sampling frequency of the instruments and acquisition rates are highly important for the quantification of unsteady turbomachine performance. In the absence of fast, responsive sensors for monitoring mass flow and temperature, however, appropriate considerations would have to be taken into account when making estimates of turbine performance under pulsating flows. A 1D model of the engine gas-stand has been developed and validated against experimental data. A hybrid unsteady/quasi-steady turbine model has been adopted to identify unsteadiness at the turbine inlet and outlet. To evaluate isentropic turbine efficiency and reduce the influence of external heat transfer upon measurements, the turbine inlet temperature has been measured experimentally in the vicinity of the turbine rotor in the inlet section, upstream of the turbine tongue. The hybrid unsteady/quasi-steady turbine model considers the presence of unsteady flows in the turbine inlet and outlet, leaving the rest of the turbine to react quasi-steadily. Virtual sensors and thermocouples have been implemented in a 1D model to correlate experimental time-averaged temperature measurements.